Keadilan Restoratif dalam Kasus Perundungan oleh Anak: Upaya Pemenuhan Asas Keadilan bagi Korban - Alisya Candra, Shahna; Handayani, Trini; Mulyana, Aji (Indonesian Journal Publisher, 2025)
The phenomenon of bullying perpetrated by minors is a serious problem in the child protection system, for both perpetrators and victims. This study aims to analyze the application of restorative justice as a resolution approach in cases of bullying by children, and to assess the extent to which this approach is able to fulfill the principle of justice for victims. The method used in this study is a normative-empirical legal type with a focus on a descriptive qualitative approach from various sources of legal norms, such as laws, court decisions, and related legal literature. The results of the study indicate that the restorative justice approach can provide a more humane and inclusive solution than the conventional criminal justice system. Restorative justice encourages recovery for victims and promotes responsibility and behavioral improvement from child perpetrators. However, the implementation of restorative justice still faces various obstacles and constraints, such as a lack of consistent law enforcement, limited facilities in fulfilling the legal system, and minimal involvement of community institutions. The conclusion of this study states that although restorative justice has excellent potential in resolving the phenomenon of child bullying that occurs in Indonesia fairly between perpetrators and victims. However, its implementation and success are highly dependent on the involvement and cooperation between legal institutions, education, society, and families in order to achieve appropriate recovery for the victim and proper rehabilitation for the perpetrator.